Partnerships to expand worksite wellness programs - A qualitative analysis of state and local health department perspectives - Christine M. Kava PhD, MA; Michelle Strait MSW, MPH; Meagan C. Brown PhD, MPH; Kristen Hammerback MA; Jeffrey R. Harris MD, MPH, MBA; Jeanne Alongi DrPH, MPH; Peggy A. Hannon PhD, MPH (SAGE Publishing, 2022)
Chronic diseases such as heart disease, cancer, and diabetes are the leading causes of death and disability in the U. S. Because the central mission of state and local health departments (HDs) is to protect, promote, and improve population health, these agencies are well-positioned to address risk behaviors for chronic disease. HD-employer partnerships could enhance worksite wellness programming, but few studies have explored this topic. Building upon previously published findings, the purpose of this qualitative study was to describe the context and environment for HDs' delivery of worksite wellness programs, including interest, barriers, facilitators, and decision-making processes. We conducted 12 interviews with directors of state chronic disease programs, 21 interviews with local directors, and three focus groups with local staff. We performed a thematic analysis of the data. Key themes include the following: (1) worksite wellness programs delivered by HDs were diverse in topic and scope and delivered both internally (at the HD for their agency) and externally (for other employers); (2) decisions made about chronic disease prevention were largely driven by funding priorities, with federal, state, and local entities playing roles in the decision-making process; and (3) HDs expressed potential interest in worksite wellness program delivery, dependent upon staff capacity, available funding, and employer buy-in. Our results suggest that funding should be increased for and reallocated towards chronic disease prevention, including worksite wellness. To overcome HD barriers to program delivery, key funders and stakeholders should prioritize and communicate the importance of worksite wellness.